Influence of surgical guide support and implant site location on accuracy of static Computer‐Assisted Implant Surgery. Issue 11 (20th August 2019) - El Kholy, Karim; Lazarin, Rafael; Janner, Simone F. M.; Faerber, Karin; Buser, Ramona; Buser, Daniel
Abstract: Objective: To investigate the effect of surgical guide support and implant site location on the accuracy of static Computer‐Assisted Implant Surgery (sCAIS) in partially edentulous patients. Materials and Methods: 375 replica implants were inserted in 85 study models. Surgical implant placement was done using static 3D printed surgical guides, which were designed to be supported either by all the teeth present in the model (full arch), or by 4‐teeth), 3‐teeth or 2‐teeth. Each study model included three single‐tooth gap (STG) situations; one extraction socket site and two implants placed in a distal extension situation. Preplanned and postoperative implant positions were compared using the treatment‐evaluation tool in digital software. 3‐dimensional and angular deviations were measured. Statistical analysis was done using ANOVA, and pairwise t tests and Bonferroni‐Holm's adjustment were applied as a post hoc test. Results: Accuracy of surgical guides used in sCAIS was significantly affected by the number and type of teeth used for its support. Guides supported by 4 teeth were not significantly different from accuracy of full‐arch‐supported guides ( p > .05). Guide support by posterior teeth was associated with an increased level of accuracy, when compared to anterior teeth guide support. Implants placed in extraction sockets were associated with significantly higher 3D and angular deviation values ( p < .05), and surgical guides with a distal extension situation resulted in significantly higher deviation values ( p < .05). Conclusion: The number and location of teeth supporting the surgical guide can significantly influence the accuracy of sCAIS, with 4 teeth providing equal accuracy to full‐arch guides in (STG) situations.